Trocar-Assisted, Sutureless, Scleral-Fixated Intraocular Lens Implantation Combined With Penetrating Keratoplasty. Issue 9 (September 2016) - Karadag, Remzi; Bayramlar, Huseyin; Azari, Amir A.; Rapuano, Christopher J.
Abstract : Purpose: To evaluate the results of trocar-assisted, sutureless, scleral-fixated (SSF) intraocular lens (IOL) implantation combined with penetrating keratoplasty (PKP). Methods: This study comprised 4 eyes (4 patients) undergoing trocar-assisted SSF-IOL implantation during PKP. The combined technique was performed in 3 eyes of 3 patients with bullous keratopathy and in 1 eye with central corneal opacity. Two eyes had anterior chamber IOL implants, and 2 were aphakic. All eyes had inadequate capsular support. Evaluated parameters were biomicroscopy, corrected distance visual acuity, intraocular pressure, IOL position, and corneal graft status. Intraoperative and postoperative complications and additional surgeries were recorded. Results: The mean follow-up period was 28.3 ± 3.5 months. Trocar-assisted SSF-IOL implantation with PKP was successfully performed in all eyes. Visual acuity improved in all patients. During the follow-up period, a well-stabilized IOL without any IOL-related complication was obtained in all eyes. In one eye with corneal scarring and aphakic glaucoma caused by trauma, drug-resistant glaucoma developed 6 months after surgery requiring Express glaucoma shunt surgery. In one eye with a history of central retinal vein occlusion, repeat keratoplasty was performed after 10 months because of graft rejection. Conclusions: Trocar-assisted SSF-IOL implantation combined with PKP is an alternative method for visual rehabilitation in the eyes with bullous keratopathy and corneal scarring without sufficient capsular support.